The perceived impact of an HIV cure by people living with HIV and key populations vulnerable to HIV in the Netherlands: A qualitative study - Kim A.G.J. Romijnders; Laura de Groot; Sigrid C.J.M. Vervoort; Maartje G.J. Basten; Berend J. van Welzen; Mirjam E. Kretzschmar; Peter Reiss; Udi Davidovich; Ganna Rozhnova (Elsevier, 2022)
Introduction: When an HIV cure becomes available, it will have consequences for people living with HIV (PLHIV) and key populations who are vulnerable to HIV. This qualitative study aimed to explore the perceived impact of two HIV cure scenarios (post-treatment control when HIV is suppressed without the need for ongoing antiretroviral treatment (ART) and complete HIV elimination) on the quality of life of PLHIV and key populations living without HIV in the Netherlands. Methods: Participants were purposefully sampled from the Amsterdam Cohort Studies, the AGEhIV Cohort Study, the outpatient clinic of the University Medical Centre Utrecht and the Dutch HIV Association to increase variability. Semi-structured in-depth interviews were conducted between October 2020 and March 2021 and thematically analysed. Results: Of the 42 interviewed participants, 29 were PLHIV and 13 represented key populations (i.e., men who have sex with men and people injecting drugs). Both PLHIV and participants from vulnerable key populations hoped that a cure would result in normalization of their lives by removing the need to disclose HIV, reducing stigma and guilt, increasing independence of ART, and liberating sexual behaviour. Both groups believed only HIV elimination could accomplish this desired impact. Conclusions: While the post-treatment control scenario seems a more plausible outcome of current HIV cure research, our findings highlight that participants may not perceive it as a true cure. Involvement of PLHIV and vulnerable key populations in devising acceptable and feasible experimental approaches to HIV cure is essential to ensure their future successful implementation.